2021
DOI: 10.22141/2224-0586.1.88.2018.124981
|View full text |Cite
|
Sign up to set email alerts
|

Особливості Перебігу Комбінованих Отруєнь «вуличним» Метадоном

Abstract: Авторами досліджені пацієнти, які проходили лікування з приводу гострих отруєнь нелегальним метадоном у Київській міській клінічній лікарні в період 2005–2017 років. Досліджено структуру отруєнь та її динаміку за 12 років. Доведено, що випадки отруєнь пов’язані з внутрішньовенним уживанням нелегального, або «вуличного», метадону. Жодного випадку отруєння медичним метадоном за період дослідження не було зареєстровано. Встановлено, що кількість даного виду отруєнь зростає та не має тенденції до стабілізації. Дос… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studying the reports of the toxicology departments and the Forensic Bureau, we found that during the last years in Kyiv among drug users, one of the most common combinations is methadone and alcohol [63][64][65][66]. However, toxicological screening proves that the biological tissues of a corpse often show non-lethal concentrations of several toxic substances in the absence of signs of injuries and diseases that could lead to death.…”
Section: Modern Features Of Epidemiology Clinical Laboratory and Path...mentioning
confidence: 99%
“…Studying the reports of the toxicology departments and the Forensic Bureau, we found that during the last years in Kyiv among drug users, one of the most common combinations is methadone and alcohol [63][64][65][66]. However, toxicological screening proves that the biological tissues of a corpse often show non-lethal concentrations of several toxic substances in the absence of signs of injuries and diseases that could lead to death.…”
Section: Modern Features Of Epidemiology Clinical Laboratory and Path...mentioning
confidence: 99%